A 7-Year Trend of Malaria at Primary Health Facilities in Northwest Ethiopia. (29th January 2020) - Addisu, Ayenew; Tegegne, Yalewayker; Mihiret, Yenesew; Setegn, Abebaw; Zeleke, Ayalew Jejaw
Abstract : Background . Malaria is a severe parasitic disease that can progress to complications of the nervous system, respiratory distress, renal problems, metabolic acidosis, and hypoglycemia which can result in death in case of delay or absence of appropriate treatment. Even though health service facilities and vector control strategy in the community are implemented as control measures, variations in temperature and rainfall that can affect the life cycle of parasite are among the factors of malaria prevalence over the years. The aim of this trend analysis was to assess the prevalence and the impact of malaria over the seasons and years. Methods . A cross-sectional study using retrospective information was conducted at two health centers Gorgora and Chuahit in Dembia district. The data was collected from lab logbooks routinely diagnosed and registered for seven years. A systematic sampling technique was used by taking patient results from lab logbooks during the first ten days of every month. Data were entered directly into the EpiData Entry software version 3.1 and analysed with the SPSS software version 20. Moreover, a chi-square test with a level of significance set at less than 5% was used. Results . From a total of 11, 879 clients that participated, 56.6% were males. The overall malaria prevalence in the last seven years was 21.8%, and the dominant parasite was P. falciparum which accounted for 15.6% of the participants which was threefold higher than P. vivax in the seven-year trend. Moreover, at Gorgora health center, the prevalence which was 15% at the beginning of the study (2012) rose to 33.9% and 30.5% in 2017 and 2018, respectively. In the analysis of the seven years, October and September in which the prevalence of malaria was 32.6% and 27.2%, respectively, constituted the peak months. High malaria prevalence was observed in autumn (September to November) season, and the least was observed in spring (March to May) with the prevalence of (17.8%) (p ≤ 0.001 ). Malaria attack showed significant variability among different age groups, and the age group 15-29 and males were the most affected (p ≤ 0.001 ). Conclusion . In this study, malaria transmission remained high, which affected males more than females. Thus, appropriate season-based bed net use, health education, immediate patient treatment, and stagnant water drainage methods are needed to alleviate the problem.